(untitled) (CIPEEX, 2025)
According to Hilgert and Slob (2019), accessibility is a right, and legislation sets forth clear provisions for eliminating barriers and implementing accessibility measures that facilitate access for people with disabilities to public spaces, buildings, furniture, and health services. This research aimed to investigate and analyze the accessibility difficulties faced by people with disabilities in accessing public health services. As a research instrument, a questionnaire developed by the study’s authors was used, applied in person to 10 employees of the Public Health Unit of Nova América, GO. In the data analysis, 100% of respondents stated that the institution provides physical accessibility features, such as ramps, handrails, and adapted restrooms. However, 20% reported that the location is not prepared to provide services to clients with hearing disabilities or deafness through LIBRAS (Brazilian Sign Language), and 10% completely disagreed that the facility offers adequate services for patients with visual impairments, such as BRAILLE (a raised-dot reading system). Additionally, 30% did not agree that accessible support materials for services are provided, or that an interpreter is available when necessary. When discussing the humane and respectful contact of health professionals with people with disabilities, a positive response was observed, reaching 60% of opinions. These findings present positive perspectives regarding the care provided to people with disabilities and the impact of a solid support network offered by the public health institution itself. It is noticeable that the health unit workers, in their training, need capacity-building, courses, and incentives to seek knowledge in Sign Language and Braille, to offer more accessible treatment to the entire population. Even though the location does not provide accessibility for all disabilities, health professionals strive to make every consultation comfortable and humane with the resources available in the hospital environment. It is concluded that the public health service studied faces challenges such as communication between the staff and patients with disabilities and the need for training for professionals in caring for people with disabilities. In contrast, humanized care is highlighted as a positive aspect. Thus, the public health care provided to people with disabilities in the Municipality of Nova América, GO, can be evaluated positively in its general aspects.